Evaluation of fretting wear behavior of PEEK by analyzing the change of crystallinity: The high temperature effect. Issue 12 (8th May 2017) - Wang, Qiufeng; Wang, Yunxia; Wang, Hongling; Fan, Na; Wang, Mengjiao; Yan, Fengyuan
Abstract : In this study, the high‐temperature tribological behaviors of poly‐ether‐ether‐ketone (PEEK) under fretting wear condition have been evaluated by using a SRV‐IV oscillating reciprocating ball‐on‐disk tribometer. It can be found that the noticeable transitions of the friction coefficient and wear rate occurred when the test temperature was 150°C. Based on the observations of the morphologies of worn surfaces, the transition of wear mechanisms of PEEK actually occurred at 150°C. In addition, by investigating the change of the crystalline structure of PEEK, results showed that the wear contributed to the formation of a higher crystallinity of PEEK. The change of the crystallinity further affected the tribological behavior of PEEK. According to the result of permanganate etching, it also can be observed that the main component of plastic deformation resulting from adhesive wear was the amorphous phase. POLYM. ENG. SCI., 57:1340–1348, 2017. © 2017 Society of Plastics Engineers